Minutes of the Annual Meeting - Siegfried, John J (American Economic Review, 2000)
Election of Members to Board of Directors: The ballots were opened and counted to be 122. The Bylaws say we need 10% of the homeowners to hold an election, which is 98.7. Three seats needed to be filled. Ramona Steele received 119 votes, Gloria Hammond received 119 votes, Spresa Clements received 5 votes, Roy Hart received 1 vote, and Doris Swanson received 1 vote. Gloria Hammonds and Ramona Steele were re-elected. Spresa Clements was appointed to fill the vacant position until next September. Ramona and Gloria will serve a three year term of office.